The 11-Year Itch: Exploitation as Sublimation in Blonde (Joyce Carol Oates, 2000; Andrew Dominik, 2022) - Jocelyn R. Dupont (Bearing Witness: Joyce Carol Oates Studies)
The goal of this article is to discuss Andrew Dominik’s much-criticized adaptation of Oates’ novel Blonde (2000), released on the Netflix streaming platform in September 2022. It aims at re-assessing the movie in the light of its literary hypotext, which appears to have been rather unfairly left out of much of the debate surrounding the release and critical reception of the film. In a first part, this article briefly addresses the stakes of Dominik’s adaptation, which are more complex than they might seem, notably on account of the extreme iconicity of its subject, even more so than its subject matter. This will then lead to approach the thorny issue of femininity and feminism as found in Oates’ book and transposed in Dominik’s film. Then, a close transsemiotic reading of one specific particular sequence from the movie Blonde will be undertaken; i.e., the famous “Subway Grate” scene – or rather photograph – initially thought of as a publicity stunt for Billy Wilder’s 1954 romantic comedy The Seven-Year Itch, very probably one of the least memorable films of the director, but whose “silly little dress” as well as the body it both covers and reveals, have left a burning impress on the collective memories of viewers and non-viewers alike.